Influenza in Tropical Regions: Epidemiology, Viral Evolution, and Control Challenges - Ni Kadek Andining Vidya; Afra Ruchudinia Mufida; Shafira Adinda Putri; Lisra Naila Mangendara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Influenza in tropical regions circulates throughout the year, with seasonal peaks varying according to rainfall, temperature, humidity, population mobility, and local epidemiological conditions. This narrative review aims to examine influenza viral characteristics and evolution, epidemiological patterns in tropical regions, vaccination challenges, and post-COVID-19 prevention strategies. Literature was searched through PubMed, Scopus, ScienceDirect, SpringerLink, Google Scholar, and World Health Organization sources, with emphasis on publications from 2016 to 2026. Evidence indicates substantial heterogeneity in influenza seasonality across tropical settings, suggesting that vaccination timing and strain selection should be guided by local epidemiological and virological surveillance rather than a uniform Northern or Southern Hemisphere schedule. Antigenic drift remains a major challenge to vaccine–strain matching, while reassortment in influenza A viruses continues to pose a potential pandemic threat. Since March 2020, no confirmed detection of naturally circulating influenza B/Yamagata lineage viruses has been reported, supporting the transition from quadrivalent to trivalent seasonal influenza vaccines. Post-COVID-19 strategies should prioritize integrated virological and genomic surveillance, locally tailored vaccination policies, improved vaccine uptake, and strengthened human–animal surveillance in areas with zoonotic risk. Universal influenza vaccine platforms remain under development but could ultimately reduce reliance on frequent seasonal strain updates.